PERAN GREEN TRUST MEMEDIASI PENGARUH GREEN BRAND IMAGE TERHADAP GREEN BRAND EQUITY PRODUK BALI RATIH - Winangun, Made Surya; Nurcaya, Nyoman (E-Jurnal Manajemen, 2020)
Brand equity is often described as the value of a brand name that is added into a product. The higher the equity of a brand, the brand competitiveness will be stronger in the market, therefore, the equity of the brand is an aspect that must be strengthened by a company. This study aims to obtain empirical evidence about the role of green trust mediating the effect of green brand image on green brand equity. The population used in this study were all consumers in the city of Denpasar who had used Bali Ratih brand products. The method of determining the sample is done by using non-probability sampling technique with purposive sampling method. Thus, respondents numbered 100 people. The data analysis technique used is path analysis. The test results state that green brand image has a positive effect on green trust, green brand image has a positive effect on green brand equity, green trust has a positive effect on green brand equity and green trust is a mediating effect of green brand image on green brand equity Keywords: green trust, green brand image, green brand equity